2014
DOI: 10.1371/journal.pone.0084938
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting De Novo Urinary Retention after Holmium Laser Enucleation of the Prostate

Abstract: ObjectivePatients can experience urinary retention (UR) after Holmium laser enucleation of the prostate (HoLEP) that requires bladder distension during the procedure. The aim of this retrospective study is to identify factors affecting the UR after HoLEP.Materials and Methods336 patients, which underwent HoLEP for a symptomatic benign prostatic hyperplasia between July 2008 and March 2012, were included in this study. Urethral catheters were routinely removed one or two days after surgery. UR was defined as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Subsequently, HoLRP combined with transurethral tissue morcellation evolved into HoLEP. Since then, many studies on this issue have been conducted with different or even contradictory results [4] [6] . Therefore, whether HoLEP is non-inferiority, equivalence, or superiority to TURP remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, HoLRP combined with transurethral tissue morcellation evolved into HoLEP. Since then, many studies on this issue have been conducted with different or even contradictory results [4] [6] . Therefore, whether HoLEP is non-inferiority, equivalence, or superiority to TURP remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…All these reasons can result in several morbidities, including bladder neck false passage as well as ureteral orifice and bladder mucosal injuries (8,9,18). Besides, some researches reported that during the morcellation the bladder is distended to greater than maximal bladder capacity and is likely to result in postoperative voiding difficulties (19).…”
Section: Discussionmentioning
confidence: 99%
“…28 De Novo Urinary Retention De novo urinary retention is related to over-distention of the bladder throughout morcellation or myogenic damage to the detrusor muscle. 36 Therefore, it is not useful to predict the learning curve of HOLEP. 36 Trifecta -Pentafecta "Trifecta has been defined as HOLEP procedure done within 90 minutes without any change to TURP, pentafecta has been reached when patients meet the trifecta criteria without postoperative complications or stress urinary incontinence".…”
Section: Complicationsmentioning
confidence: 99%
“…36 Therefore, it is not useful to predict the learning curve of HOLEP. 36 Trifecta -Pentafecta "Trifecta has been defined as HOLEP procedure done within 90 minutes without any change to TURP, pentafecta has been reached when patients meet the trifecta criteria without postoperative complications or stress urinary incontinence". 19 The learning curve has been reached when the urologist could perform four consecutive HOLEP procedures and reach the trifecta or pentafecta criteria.…”
Section: Complicationsmentioning
confidence: 99%